2017
DOI: 10.5433/1679-0359.2017v38n4suplp2669
|View full text |Cite
|
Sign up to set email alerts
|

Influence of vitamins C and E on the quality of cryopreserved semen Prochilodus brevis (Prochilodontidae, Teleostei)

Abstract: Seminal cryopreservation allows the long-term conservation of gametes of various species, including endangered species, such as Prochilodus brevis. However, the application of this biotechnology can cause damage to sperm cells, reducing seminal quality. Thus, we have sought substances that minimize the damage caused by this process, such as antioxidants. Thus, this study aimed to evaluate the association between two cryoprotectants and two vitamins, in different concentrations, on the quality of cryopreserved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
2
3
0
3
Order By: Relevance
“…(2011), these characteristics can be influenced by several factors such as animals' nutritional status, age, weight and health status; the hormone type and dosage used in the induction process; the climate; the time of year; and the collection frequency, among others. Sperm kinetics (total motility, VCL, VSL and VAP) values recorded in the present study were similar those found in studies conducted with P. brevis (Almeida‐Monteiro et al., 2017; Lopes et al., 2014; Nascimento et al., 2017; Nunes et al., 2016).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…(2011), these characteristics can be influenced by several factors such as animals' nutritional status, age, weight and health status; the hormone type and dosage used in the induction process; the climate; the time of year; and the collection frequency, among others. Sperm kinetics (total motility, VCL, VSL and VAP) values recorded in the present study were similar those found in studies conducted with P. brevis (Almeida‐Monteiro et al., 2017; Lopes et al., 2014; Nascimento et al., 2017; Nunes et al., 2016).…”
Section: Discussionsupporting
confidence: 90%
“…According to conventional freezing studies conducted with P. brevis , 10% DMSO and 5% glucose are the best extenders for this species (Almeida‐Monteiro et al., 2017; Nascimento et al., 2017; Nunes et al., 2016, 2019). However, knowledge about whether the use of this solution is also suitable for rapid freezing remains unknown and the literature lacks reports about EG use for the semen cryopreservation of this species.…”
Section: Discussionmentioning
confidence: 99%
“…Uma variedade de substâncias antioxidantes já foi utilizada com sucesso na criopreservação seminal de teleósteos, entre elas a vitamina C, vitamina E, taurina e cisteína [1,11,13,14,19]. Apesar de já haver registros sobre o sucesso da utilização de antioxidantes na concentração de 1 mM na criopreservação seminal de teleósteo [14], nas condições empregadas nesse estudo, os resultados encontrados nos tratamentos suplementados com as substâncias antioxidantes foram, de modo geral, similares aos encontrados para o tratamento não suplementado.…”
Section: Discussionunclassified
“…Entre os antioxidantes que já apresentaram resultados positivos na criopreservação seminal de teleósteos, pode-se citar as vitaminas C (ácido ascórbico) e E (α-tocoferol), e os aminoácidos cisteína e taurina [1,6,11,14,18,19]. No entanto, não existem relatos na literatura sobre a utilização de antioxidantes na criopreservação seminal de tambaqui, incluindo os supracitados.…”
Section: Introductionunclassified
See 1 more Smart Citation